INVESTIGATION THE ROLE OF GDF-15 AND ARFIP2 LEVELS IN TYPE 2 DIABETIC PATIENTS A COMPARATIVE GENDER-BASED STUDY - Jabbar, Hameedah A.; Thuwaini, Mahdi M.; Al Sawafi , Abeer (International Journal Multidisciplinary (IJMI), 2026)
Objective: The present study seeks to evaluate the quantification of serum levels of ADP-ribosylation factor-interacting protein 2 (ARFIP2) and growth differentiation factor-15 (GDF-15), as well as to investigate potential correlations between these factors and glycaemic control metrics and insulin resistance (HOMA-IR), in order to elucidate their roles in the pathophysiology and progression of diabetes mellitus (DM). Method: The case-control study included 111 individuals, consisting of 51 patients diagnosed with diabetes mellitus and 60 healthy individuals serving as a control group. We measured the levels of GDF-15 and ARFIP2 in two study groups, as well as the levels of serum glycaemic markers (FBS, Insulin, HbA1c) and HOMA-IR. Results: In T2DM, ARFIP2 showed significant correlations with FBS, insulin, and HOMA-IR suggesting its role in insulin resistance and acute glycemic regulation but showed limited associations in controls, indicating its role becomes more pronounced under diabetic conditions. GDF-15 showed a positive but non-significant correlation with ARFIP2, hinting at a possible shared pathway in metabolic stress and inflammation but in control group showed a highly significant correlation suggesting it may act as an early biomarker of metabolic stress. Novelty: ARFIP2 is strongly associated with insulin resistance and acute glycemic markers in T2DM, but not with long-term glycemic control. GDF-15 shows strong associations in controls and trends in T2DM, suggesting it may serve as an early stress-response biomarker. Gender differences in distribution were observed but not statistically significant, indicating the need for larger sample sizes to clarify gender-specific biomarker patterns.